The pursuit of new role: A study of luxury products consumption during the liminal transition into first time employment - Chucherd, Sunong (2008)
Consumer behaviour research on role transition has so far been limited to the negative life changes and the changes-specific consequences towards the consumption pattern. Moreover, although young adult customers have recently been the new target customer for many luxury brands, no research has been conducted concerning the impacts of role transition during the transition into first-time employment and the role of luxury products in dealing with those effects. Liminal transition is also a new area worth investigating because it shows the harmful effects and instability in an individual's self-concept. Also, it is widely acknowledged that the more insecure liminal consumers are, the more likely they will rely on symbolic consumption to reinforce a perception of adequate role performance.